Beyond Ubuntu: Nnoboa and Sankofa as Decolonizing and Indigenous Evaluation Epistemic Foundations from Ghana - Douglas Asante; Thomas Archibald (The Evaluation Center at Western Michigan University, 2023)
Background: Evaluation is an increasingly vital component of community and economic development projects in Africa. Yet questions remain about how relevant most evaluation approaches for the African evaluation context. Within the 'Made in Africa' (MAE) approach, ubuntu is frequently cited as an African philosophical concept with salience to MAE. There is a need to further expand and explicate other African philosophies that can serve as epistemological guideposts for African evaluation-and other decolonizing, indigenous evaluation approaches more broadly. Purpose: Drawing on Ghanaian epistemologies and frameworks, the purpose of this paper is to propose the Nnoboa system of communal collaboration in farming and industry, as well as the notion of Sankofa as a traditional philosophical concept that irrupts and challenges hegemonic Eurocentric notions of the linearity of time, to yield a Ghanaian indigenous knowledge of evaluation. Setting: Not applicable. Intervention: Not applicable. Research Design: This conceptual study draws on literature on culturally responsive evaluation (CRE), MAE, and (from beyond the field of evaluation), descriptions of Nnoboa and Sankofa to propose a conceptual synthesis applicable to decolonizing, indigenous evaluation. Data Collection and Analysis: Not applicable. Findings: We propose that Nnoboa and Sankofa represent an addition to the decolonizing and indigenous evaluation knowledge base, building on and going beyond the reliance of CRE and MAE in ubuntu. We propose this Ghanaian approach has potential applications across MAE and CRE more broadly.